Social Construction and Relationalism: A Conversation with Kenneth Gergen - Aceros, Juan C.; Departament de Psicologia Social, Universitat Autònoma de Barcelona (2012)
Kenneth Gergen is one of the most widely known contributors to social constructionist thought in the world today. Since the publication of his paper “Social Psychology as History” he has become a central player in what is known as the Social Psychology Crisis. In his academic career, and from what he has called ‘Relational Theory’, Gergen has revisited a significant number of psychological constructs and has proposed various dialogical and collaborative practices in therapy, organizational development, education, community development, social work and peace-building, among other things. This paper is a conversation with Gergen in which together we explore the particular way in which he understands the social constructionist movement. It is also a conversation about relational theory and related practices.